Analysis of current Governance in the Sustainable Management of the Virunga National Park of the Democratic Republic of Congo - Jean-Pierre, Bulambo Milenge; Ali Shidiki, Abubakar; N. Tchamba, Martin (International Journal of Forest, Animal and Fisheries Research, 2021)
This study was carried out in Virunga national park (ViNP) of the Demographic Republic of Congo. The study had as objective to contribute to the sustainable management of the Virunga national park. The study area was made up of four (4) administrative territories (Masis, Goma, Nyiragonga and Rutshur); these territories are found in the North KivProvence of the democratize Republic of Congo.Data was collected through the administration of 394 structured questionnaires to household heads residing around the peripheries of the Virunga national park. The data was imputed into a Microsoft excel sheet 2016 and was analysis using an SPSS version 21 statistical package. The results revealed that majority of respondents were youths 86% with ages below 61years. On the question; on the collaboration between local population and park management, the results showed that 76.4% of respondents had no form of collaboration with park management. The results also revealed that majority of respondents do not participate in the management of the ViNP. The presence park governance is highly contested by the local communities and should be revise to incorporate the concerns of the local population. To revive the lost trust and improve the relationship between the local populations living around the park and the management of the park; locals populations should participate in the management of the national park; benefit from park resources should be share and alternative income activities be created to prevent youths from relying on the park resources as a livelihood source.